Drugs affecting HbA1c levels - Unnikrishnan, Ranjit (Medknow Publications & Media Pvt Ltd, 2012)
Glycated hemoglobin (HbA1c) is an important indicator of glycemic control in diabetes mellitus, based on which important diagnostic and therapeutic decisions are routinely made. However, there are several situations in which the level of HbA1c may not faithfully reflect the glycemic control in a given patient. Important among these is the use of certain non-diabetic medications, which can affect the HbA1c levels in different ways. This review focuses on the non-diabetic medications which can inappropriately raise or lower the HbA1c levels, and the postulated mechanisms for the same.